Implications Of Cash Flow Forecasting On Highway Projects In Iraq - Ismail Al Hadithi, Bevian (Anbar Journal of Engineering Sciences, 2016)
The cash flow forecasting is beneficial for the project in both the tender stage and during the project construction progress, where the contractors want to make sure that their planned cash funds is sufficient to cover any possible financial deficit of the project. This research aims to find out minimum fund needed for highway projects in Iraq required by the contractor to maintain the progress of work under some circumstances and effects of the shortage of fund, particularly in case of payment delay, in addition to the implication of the payment delay. Data from record files of 9 highway projects in Iraq, of the unit price type contracts. It was found that the minimum fund required is 20.944 percent of the contract value of three months delay . The minimum fund required for those projects is directly proportional to the time of payment delay. The minimum fund required for projects is represented in a linear equation as a function of payment delay time, such equation would help the contractor to estimate the future amount of minimum fund required for any delay in months. Interim profit is calculated for the purpose of comparison with the expected profit for the purpose of exploring the consequences in case exceedance. Because of the use of unit price contracts in the implementation of highway projects in Iraq, it did not cause the appearance that the contractor receives large profit at early stages of the project. The delay in payment leads to negative results, including the delay in the project, reduces the level of performance of the contractor which is negatively affects project, reduce the quality of implementation and, increased cost of the project in case of the contractor to claim compensation for the damage, as well as the occurrence of a difference in currency and inflation due to the time difference between the payment date and the actual date.